Design, analysis, and fabrication simplified drain wastage cleaner device / Muhammad Ikram Hafiz Zaidi Farouk - Zaidi Farouk, Muhammad Ikram Hafiz (2022)
Introducing or implementing new ideas or methods is not the only way to demonstrate innovation. The definition or meaning of innovation can be defined as a multi-step process that helps new ways of doing things. Currently, the expansion of drain cleaning in Malaysia still using the old method. Therefore, there are a lot of problem that worker or people need to face when cleaning the drain. Simplified Drain Wastage Cleaner is an innovative device inspired by the existing project that made by students from other countries. This concept should be implemented in Malaysia. So, this innovative will help the workers or people easily to clean the drain. Other than that, this device will give more benefit to everything including environment, animals, and human. For instance, this device is easy to operate and will help the workers to reduce their times and energy during the cleaning process. Moreover, this device will be sold at a reasonable price. This devices marketing is focused on society especially residential area, school, and public playground.